PENTINGNYA MENGENAL KARAKTERISTIK DAN KLASIFIKASI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - irwana, dea; Andriani, Opi; eriska, hilda; kurniya, budi; rahmadani, nova dwi (Jurnal Pendidikan Vokasi dan Seni, 2025)
This study aims to identify the characteristics and classifications of children with special needs (CSN) in elementary schools. The research employs a literature study approach. Understanding the characteristics and classifications of CSN in elementary schools is a critical aspect of supporting the success of inclusive education. Children with special needs possess unique traits that influence their ways of learning, interacting, and developing, requiring educational approaches that differ from those of typically developing children. This study explores the importance of an in-depth understanding of CSN characteristics, including physical, intellectual, emotional, and social challenges, as well as the benefits of grouping or classifying their specific needs, such as visual impairments, hearing impairments, autism, ADHD, and learning difficulties. By recognizing the characteristics and classifications of CSN, teachers can design more effective teaching strategies, provide appropriate facilities, and create an inclusive learning environment. Additionally, this understanding facilitates collaboration between teachers, parents, and specialists to support the academic, social, and emotional development of children.